The Effect of Learning Methods, Extracurricular Activities, and Perceptions in the Campus Environment on Character Motivation of Student - Andy Wahyu Hermanto; Tamsik Udin; Sudirman Sudirman (Postgraduate, University of Mataram, 2023)
Many cadets still cannot manage their sleep time properly, thus affecting their study patterns and time. The schedule for extracurricular activities is quite tight, so the rest time for cadets is reduced. This results in decreased motivation to learn. This study aims to analyze the influence of learning methods, extracurricular activities, and perceptions in the campus environment on the character motivation of cadets of the Politeknik Ilmu Pelayaran (PIP). This study uses a quantitative approach and the population of this study was all cadets totaling 450. The sampling technique used was the Slovin formula, so the number of samples used in this study was 229 cadets. Data collection techniques using a questionnaire through Google form. The data analysis technique uses the SPSS version 21 programs. The results of this study indicate that learning methods, extracurricular activities, and perceptions of the campus environment significantly affect the basis of the Cadets' character. Motivation with the character of Cadets can increase when learning goes well, and extracurricular activities can also be carried out well. The perception of the campus environment is good. Learning methods, extracurricular activities, and perceptions of the campus environment significantly affect the motivation of the Cadets' character. This means that reason with the nature of Cadets can increase when learning goes well, and extracurricular activities can also be carried out well. The perception of the campus environment is good too